HERMENEUTIKA AL-QUR`AN AMINA WADUD MUHSIN - aniqoh zuhri (IAIN Madura, 2021)
Al-Qur'an has an important position in Islamic studies, beyond its function as a guidance, Holy Qur'an also functioned to be a differentiator. In interpreting hermeneutics, this is a form of interpretation method which in its operation is used to derive conclusions about the meaning of a text or verse. According to Amina Wadud, there is no truly objective method of interpreting the Qur'an. Each commentator sets several subjective choices. In Islamic studies, there are several approaches offered by intellectuals to get the moral message of Islam as a religion that has a gender perspective. Here the author attempt to discuss several examples of Amina Wadud's interpretation with her hermeneutical model regarding the issue of women's rights and roles. The aim is to evaluate the extent to which the position of women in Muslim culture has truly reflected the meaning of Islam regarding women in society. In addition, the specific goal is to demonstrate the ability to adapt the worldview of the Qur'an to women's issues according to the modern context. The author argues that the ultimate purpose of the theory is to build a harmony among of Islamic teaching: law, ethics, and theology, each of which has to support one another.